STRUCTURЕ-FUNCTIONAL FEATURES OF BLOODSTREAM AND PARENCHYMA OF MALES’ TESTIS AND EPIDIDYMIS - Hotiur, O.I. (World of Medicine and Biology, 2012)
The state of the bloodstream and testicular parenchyma and epididymis in men 36-59 years of testis investigated. Found, that only 62% of the convoluted seminiferous tubules of the testis remain common device, in the other founded different degree of damage of the spermatogenic epithelium and focal deformation of the grid haemomicrovascular rate. Similar histostructural changes were found in microvascular rate and extension ducts of epididymis.
Keywords: testis; epididymis; interstitial cells